Molecular dynamics insight of interaction between the functionalized-carbon nanotube and cancerous cell membrane in doxorubicin delivery. (March 2023) - Kordzadeh, Azadeh; Zarif, Mahdi; Amjad-Iranagh, Sepideh
Highlights: Molecular investigation of doxorubicin (DOX) encapsulation on folic acid and carboxyl functionalized carbon nanotubes is being studied. Folate receptor embedded bilayer was selected as a modelof cancer cell, and the morphology change of bilayer after drug release was investigated. Comparison of drug release from carboxyl and folic acid-functionalized carbon nanotubes in the vicinity of cancer cells is carried out Functionalization of carbon nanotubes with folic acid by two mechanisms sensitive to pH and ligand improves the drug release near cancer cells. Abstract: Background and objective: Doxorubicin (DOX) is a known anticancer drug which is widely used in cancer therapy. Carbon nanotubes (CNTs) are among the most promising platforms for smart drug delivery applications. However, due to the toxicity and their low sulubility their application is limited and their functionalization with wide range of biomolecules are suggested. Therefore, the functionalized carbon nanotubes (f-CNT) with carboxyl (CNT-COO) and folic acid (CNT-COO-FA) were investigated as drug-carrier. Methods: Molecular dynamics (MD) simulation along with the Density Functional Theory (DFT) methods are being used to study the drug loading process on functionalized carbon nanotubes. Results: The results indicate that doxorubicin molecules interact more with CNT-COO-FA than CNT-COO. The embedded dipalmitoylphosphatidylcholine (DPPC) lipid bilayer with a folate receptor was considered a cancerous cell's representative model. Then the drug release from the f-CNTs near the lipid bilayer was simulated. The results showed that CNT-COO-FA with a pH and ligand-sensitive mechanism strongly interacts with cancerous cells, which led to higher drug release, in agreement with the experimental results. The conformational changes of the lipid bilayer and folate receptor during drug release were evaluated. The analysis showed that drug release from CNT-COO-FA has significantly changed lipid bilayer and receptor conformations. The obtained results were interpreted and justified by considering the molecular mechanisms which control the drug delivery in the studied systems. Conclusions: Based on the obtained results, CNT-COO-FA has a better performance during the drug release compared to CNT-COO in delivering doxorubicin. Both pH and ligand sensitive mechanisms are found to be responsible for higher drug delivery efficiency of CNT-COO-FA. In contrast, CNT-COO can only enhance drug delivery efficiently with a pH-sensitive mechanism.